Essential oils of the genus Pereskia: a literature review (Research, Society and Development, 2020)
Several scientific studies have revealed pharmacological properties associated with species of the genus Pereskia. However, so far, little is known about the chemical composition of the essential oils of plants of this genus. Thus, this study sought to carry out a bibliometric and bibliographic review on the scientific production related to the chemical composition of the essential oils of these plants. The information used in this study was obtained from different databases available online. Using specific descriptors, along with the PRISMA methodology, three scientific studies were selected (two articles and one dissertation). The oxygenated diterpene known as phytol proved to be one of the major components of the essential oils of both species of this genus: P. grandifolia and P. aculeata. Manool oxide was considered the component with the highest concentration in the essential oil of P. grandifolia, while the contents of linoleic acid and acarone stood out in the essential oils of P. aculeata. It was possible to evaluate the grouping of samples of the genus Pereskia, based on the chemical composition of its essential oils, with the aid of the multivariate analysis tool known as ACP (Principal Component Analysis).